1991
DOI: 10.1177/0145482x9108500205
|View full text |Cite
|
Sign up to set email alerts
|

Are Social Skills Teachable? A Review of the Literature

Abstract: This article reviews studies that have attempted to increase three types of social skills in blind and visually impaired individuals: assertiveness training, interactional skills, and skills in physical communication. Each study is described briefly, and the procedures and results are noted. Most of the studies reported increased social skills following intervention; however, many did not report empirical evidence of change. The articles also demonstrate a need for the follow-up and generalization of learned s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In an inquiry classroom gifted students with visual impairments can be placed in situations in which they demonstrate their superior problem solving and thinking skills, thus increasing their selfesteem. Because research indicates that appropriate social skills can be a problem for both students who are gifted (Borland, 1989) and students with visual impairments (Erin, Dignan, & Brown, 1991;Sacks, Kekelis, & Gaylord-Ross, 1992), development of skills in working with other students should occur in the context of inquiry learning. Teachers will need to focus, however, on helping students develop these skills rather than assuming the students will learn them on their own.…”
Section: The Gifted Visually Impaired Learnermentioning
confidence: 99%
“…In an inquiry classroom gifted students with visual impairments can be placed in situations in which they demonstrate their superior problem solving and thinking skills, thus increasing their selfesteem. Because research indicates that appropriate social skills can be a problem for both students who are gifted (Borland, 1989) and students with visual impairments (Erin, Dignan, & Brown, 1991;Sacks, Kekelis, & Gaylord-Ross, 1992), development of skills in working with other students should occur in the context of inquiry learning. Teachers will need to focus, however, on helping students develop these skills rather than assuming the students will learn them on their own.…”
Section: The Gifted Visually Impaired Learnermentioning
confidence: 99%
“…Johnson and Johnson (1991), using a pre-post two-group de sign, reported that participants who re ceived group counseling had greater gains in self-concept, more favorable attitudes toward blindness, and a more internal lo cus of control than did participants in the comparison group. Kim (2003) (Erin, Dignan, & Brown, 1991;McDon nall, 2011;McDonnall & Crudden, 2009;Shaw, Gold, & Wolffe, 2007).…”
Section: Social Skills and Self-conceptmentioning
confidence: 99%
“…Social Skills. Research has indicated that students with visual impairments are behind their peers without impairments in social skills development (Erin, Dignan, & Brown, 1991). Without the benefit of certain visual cues, some students may not have learned behavior appropriate in social situations.…”
Section: Impairments If They Can Be "Read" Using the Sense Of Touchmentioning
confidence: 99%